How can we improve the diagnosis and management of bladder pain syndrome? Part 1: ICI-RS 2018 - TARCAN, TUFAN (WILEY, 2019)
Background This paper summarizes the discussion in a think tank at the ICI-RS 2018 about the diagnosis of bladder pain syndrome (BPS). Aims To review the guidelines, investigations and subtypes of BPS. Materials and Methods Review of literature in the light of the think tank discussion. Results All guidelines recommend completing history, physical examination, urine analysis, urine culture, and urine cytology to define the BPS phenotype but there are differences on further investigations. In those guidelines which recommend cystoscopy, the identification of Hunner's lesions (HLs) is recommended as this changes the treatment plan and outcome. Conclusion We propose that the differentiation of Hunner's ulcers is an important step in the assessment of these patients. Further suggestions for research are suggested.
Keywords: cystoscopy; imaging; investigation; magnetic resonance imaging; painful bladder syndrome; urinary frequency; INTERSTITIAL CYSTITIS; CYSTOSCOPIC FINDINGS; HUNNER LESION; WOMEN; SYMPTOMS; SUBTYPE; MRI